An ethnomethodological view of bargain shopping in Greenhills tiangge - Sucgang, Khristine M. (2011)
This is an observational study on culture and consumer behavior in a triangle. It looked at shopping norms and practices constituting bargain shopping as a socially-organized activity. Using ethnomethodology as lens for investigating everyday, practical activities, this study examined the membership, talk, and conduct of shoppers in Greenhills triangle. Participant observation was used to explicate various aspects of the phenomenon under study. Findings revealed that bargain shopping appealed to a wide range of consumers regardless of age, gender, and socio-economic class. It consisted of a set of procedures from product search to inquiry, seeking out and later evaluating alternatives, haggling, and finally purchase. The informal nature of triangle shopping cultivated a relaxed environment for more personal, one-on-one interactions between vendors and buyers. Talk was generally light and cordial with the vendor engaging in the interaction more than the buyer. Bargain shopping was primarily constituted as a leisurely social activity, one that necessitated time and effective communication skills and was best suited for people in high-context cultures, such as the Philippines.
Keywords: Shopping centers; Shopping centers -- Social aspects; Bargain shopping